Aerobic exercise in depressed youth: A feasibility and clinical outcomes pilot. Issue 1 (26th January 2018) - Jaworska, Natalia; Courtright, Allegra K.; De Somma, Elisea; MacQueen, Glenda M.; MacMaster, Frank P.
Abstract : Aim: Major depressive disorder (MDD) onset generally occurs in adolescence/early adulthood. However, pharmacotherapy use in younger populations is restricted due to black box warnings. Aerobic exercise may be a viable treatment option for mild‐to‐moderate MDD, but little is known about its acceptability/effectiveness in young adults. Methods: Unmedicated and relatively inactive 18‐to‐24 olds with MDD completed fitness/clinical assessments at baseline and after 12 weeks of supervised aerobic exercise (3×/wk; 30‐minute sessions in target heart rate [HR] zone), with the aim of increasing cardiovascular fitness (VO2max ‐indexed). Results: Post‐intervention, predicted VO2max increased, whereas depression scores decreased. A correlation existed between time spent in target HR zone and anxiety symptom decreases. Exercise adherence and satisfaction were high, and drop‐out was minimal. Conclusions: This pilot is among the first to assess the feasibility of aerobic exercise as an antidepressant treatment strategy in young adults, a group for which options have limited acceptability.